PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UN CENTRO DE TERAPIA FÍSICA PARA MUJERES EMBARAZADAS, UBICADO EN EL CANTON CATAMAYO, PROVINCIA DE LOJA - Gaona Sánchez, Gloria Patricia (2015)
The thesis entitled: "PROJECT FEASIBILITY FOR BUILDING CENTER PHYSICAL THERAPY FOR PREGNANT WOMEN, LOCATED IN THE CATAMAYO CANTON, LOJA PROVINCE", aimed at presenting a proposal to determine the feasibility of the project to be created. The same will be facing both economic and social development of the canton, province and country. The overall objective of this study is to determine the feasibility of the project, and based on this the specific objectives were developed to establish market studies, technical, administrative and legal, economic and financial study and finally the evaluation. The methodology used to achieve the objectives referred to deductive method from the general to the particular, and the inductive part of the particular to the general. In the study of market demand and supply was analyzed for this survey was conducted to potential applicants for the use of this service.These allow for greater amount of quantitative data existing phenomena for further systematization and analysis. Due to the length of the population, a sample was drawn, the sampling technique was used whose base is the population that visit, (Catamayo) (13,120 women) and a margin of error of 5%. It was applied according to the sample 388 surveys in the city of Catamayo urban sector, which will allow the development of Market. Therefore determine our potential customers.The results determined in this study are: Market research determines that the potential of the project in 2014 demand is 26.240 women, there is not the actual demand, and the effective demand is 24.666. Technical Study which is based on the installed capacity is 21.900 which represents 100%, the capacity utilization is of 6.240 which represents 28% of the installed capacity for the first year, location geographic physical Therapy Center is in the city of Catamayo in the streets Simon Bolivar street between May 1 and Av. Catamayo which is in a strategic location and extent of our applicants. Within the financial study it found that the initial investment for the project is $ $21.481,68 the same as finance from internal sources in the amount of $ $11.481,68 or 53%, and external source $ 10.000, equivalent to 47 % to be paid by the NATIONAL BANK OF DEVELOPMENT whit the percentage of 11.20%. The financial evaluation allowed to have the following results in the financial evaluation, the following results were determined: Net (NPV) Present value is $63.771,28. Internal Rate of Return (IRR) is 74,61%. Benefit Cost Ratio (RB / C) it is $ 1.49. The Capital Recovery Period (PR / C) is achieved in 1 year, 10 months with 16 days, the project sensitivity analysis supports an increase in costs of 25,98 % and a decrease in revenues 18,33% which It means that it is not sensitive to the variation of the changes. With all these mentioned aspects is concluded that the establishment of the company is viable, this idea of project aims at providing an alternative business, being a source of work while providing a service where the customer is satisfied in the city of Catamayo.